A blended approach to design education through clinical immersions and industry partnerships in design for healthcare - Kiernan, Louise; White, Eoin; Morrissey, Kellie (Design and Technology Education: An International Journal, 2021)
Contemporary design education seeks to prepare students for the workplace through studio-based learning that replicates real world practice. Design problems in the workplace have become increasingly complex and one example of this is within the area of design for healthcare, which requires multidisciplinary collaboration between various stakeholders to build knowledge in order to create new products, services systems and spaces. The complexity of these roles creates challenges for design educators in preparing students for the workplace. This paper presents a hybrid approach to address this challenge by presenting a real-world approach to design education. This entails a bottom-up approach to facilitate design research in a clinical setting to gather rich insights and needs of the clinical setting along with a top-down industry collaboration with sponsored briefs to guide students through the requirements of developing solutions in a heavily regulated field. The paper outlines examples of this process and how it was achieved in a blended model that was predominantly online in response to the changed environment caused by the COVID-19 pandemic.The advantages of this model are threefold, students gain deep knowledge and skills through collaborating with a variety of stakeholders within health care, they gain the opportunity to validate their designs through testing and feedback with these partners and lastly students develop the connections to create opportunities for further partnerships and employment.